CHARACTER BUILDING THROUGH MORAL ASSISTANCE IN AL AMIN ISLAMIC EDUCATIONAL INSTITUTE (TPQ) SALAMAN MAGELANG - Wafirah, Milna; Zuliyanti, Titik (Wahana Islamika: Jurnal Studi Keislaman, 2021)
Character building is crucial to preparing a good generation of the nation. There are many ways to instil character formation, including moral assistance with an Islamic approach. This study analyses character formation through the habituation of routine activities carried out at Al Amin Islamic Educational Institute (TPQ), Salaman, Magelang. This study uses a qualitative case study method. Moral assistance through routine activities at TPQ Al Amin shows a significant increase in positive character building in children.